Effects of Patagonian pine forestry on native breeding birds - Pescador, Moises; Peris, Salvador (Forest Systems, 2014)
Aim of the study: The objective is to assess the influences of the tree stand age and other forestry management practices on species richness, composition, and distribution of the Patagonian pine plantation bird assemblages. Area of Study: The work was carried out in forested plots of Ponderosa pine located at the Lanín National Park (Patagonia, Argentina). Material and Methods: Birds were sampled using 25 m fixed radius point counts, at four plots varying in age, management, and forest structure. Main Results: A total of 2090 individuals belonging to 34 bird species were observed, their numbers vary significantly depending on the different modes of plantation management. The population density of the 14 most abundant bird species was compared among the four plantation plots and ten species don’t show statistically significant differences in their population density among the different forest plots. The California Quail, the White-Crested Elaenia and the Southern House Wren showed higher densities in pine plantations with lower tree densities and fewer cutting treatments. The Diuca Finch had high densities in the younger plantations not subjected to any treatment. Research highlights: Most of these bird species are opportunistic and a few are found more regularly in these non-native woods than in other native forested or afforested areas. Our data suggest that a mixed scenario based on a mosaic of plantation with patches of native deciduous forest may help maximize the bird diversity in the management of northwestern Patagonian plantation landscapes. Keywords: Bird population; diversity; exotic plantations; Patagonia; tree-age.